2013
DOI: 10.1002/wrcr.20202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changing pan evaporation in the arid region of Northwest China

Abstract: [1] Decreases in pan evaporation (E p ) over the last decades have been reported in many regions of the world. In this study, we investigated E p dynamics in the hyper-arid region of China during the period 1958-2010 using a generic physical model based on long-term meteorological data collected at 81 ground-based meteorological stations. We also quantified the contribution of climatic factors to the E p change using partial derivatives. We found that E p in the region exhibited an obvious decreasing trend unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 40 publications
15
99
0
Order By: Relevance
“…In addition, the annual Ep registered the values of 1997, 2062, 2090 and 2087 mm, respectively, while the monthly maximum for each year was found to be about 289.4 mm (July), 293.2 mm (July), 303.9 mm (August) and 285.4 mm (July) in 2013-2016, respectively. Compared to historical mean values, the monthly Ep values were lower in the period of May-October, owing to the lower wind speed values as described in other studies (e.g., [39]), except for the month of October 2014.…”
Section: Weather Conditionsmentioning
confidence: 45%
“…In addition, the annual Ep registered the values of 1997, 2062, 2090 and 2087 mm, respectively, while the monthly maximum for each year was found to be about 289.4 mm (July), 293.2 mm (July), 303.9 mm (August) and 285.4 mm (July) in 2013-2016, respectively. Compared to historical mean values, the monthly Ep values were lower in the period of May-October, owing to the lower wind speed values as described in other studies (e.g., [39]), except for the month of October 2014.…”
Section: Weather Conditionsmentioning
confidence: 45%
“…Rivers originating in these mountains are mainly fed by snowmelt and glacier-melt water. The air temperature in mountainous areas has experienced a sharp increase over the past half-century [7,8], accompanied by accelerated snow and glacier melting as a consequence. Many studies have revealed the significant trend of glacier/snow-cover shrinkage and snowline rising occurring in Tienshan Mountains [9][10][11], and half of its total glacier volumes will catchments ranges from 298 km 2 to 43,343 km 2 , and the elevation ranges from 1049 m to 4638 m. The annual precipitation varies from 118 mm to 778 mm, and the annual pan evaporation is from 560 mm to 1202 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The GDP per capita of the HRBSP and the four cities situated nearby (that is, Heze, Zaozhuang, Jining and Linyi) is expressed as the economic factor, and the industrial wastewater discharge is expressed as the industrial load factor. According to, 33 GDP per capita in the HRBSP revealed speedy progression between 2001 and 2010 because the regression curve grew steadily but flattened later, particularly during periods exceeding 2008. The Zaozhuang and Jining cities experienced innovative economic growth that generated greater industrial wastewater discharges as against Heze and Linyi cities.…”
Section: Growth and Development Huai River Basin's Water Resourcementioning
confidence: 99%
“…The supremacy of tertiary over secondary industries gave rise to the emergence of the post-industrial phase. 33,34 In 2010, it was estimated that the GDP of the HRBSP was put at 810.14 billion Yuan. The primary, secondary, and tertiary sectors contributed 11.32%, 50.23%, and 38.46 % of the industrial arrangement in the study area, with respect to industrial outputs valued at 100.71, 430.77, and 278.66 billion Yuan.…”
mentioning
confidence: 99%